Cryogenic integrated spontaneous parametric down-conversion - Lange, Nina Amelie; Höpker, Jan Philipp; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Cryogenic electro-optic modulation in titanium in-diffused lithium niobate waveguides - Thiele, Frederik; vom Bruch, Felix; Brockmeier, Julian; Protte, Maximilian; Hummel, Thomas; Ricken, Raimund; Quiring, Viktor; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Journal of Physics: Photonics)
Abstract Lithium niobate is a promising platform for integrated quantum optics. In this platform, we aim to efficiently manipulate and detect quantum states by combining superconducting single photon detectors and modulators. The cryogenic operation of a superconducting single photon detector dictates the optimisation of the electro-optic modulators under the same operating conditions. To that end, we characterise a phase modulator, directional coupler, and polarisation converter at both ambient and cryogenic temperatures. The operation voltage <?CDATA $V_{π/2}$?> V π / 2 of these modulators increases, due to the decrease in the electro-optic effect, by 74% for the phase modulator, 84% for the directional coupler and 35% for the polarisation converter below 8.5 <?CDATA $\,K$?> K . The phase modulator preserves its broadband nature and modulates light in the characterised wavelength range. The unbiased bar state of the directional coupler changed by a wavelength shift of 85 <?CDATA $\,nm$?> n m while cooling the device down to 5 <?CDATA $\,K$?> K . The polarisation converter uses periodic poling to phasematch the two orthogonal polarisations. The phasematched wavelength of the utilised poling changes by 112 <?CDATA $\,nm$?> n m when cooling to 5 <?CDATA $\,K$?> K .
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Opto-electronic bias of a superconducting nanowire single photon detector using a cryogenic photodiode - Thiele, Frederik; Hummel, Thomas; Protte, Maximilian; Bartley, Tim (APL Photonics)
Superconducting Nanowire Single Photon Detectors (SNSPDs) have become an integral part of quantum optics in recent years because of their high performance in single photon detection. We present a method to replace the electrical input by supplying the required bias current via the photocurrent of a photodiode situated on the cold stage of the cryostat. Light is guided to the bias photodiode through an optical fiber, which enables a lower thermal conduction and galvanic isolation between room temperature and the cold stage. We show that an off-the-shelf InGaAs–InP photodiode exhibits a responsivity of at least 0.55 A/W at 0.8 K. Using this device to bias an SNSPD, we characterize the count rate dependent on the optical power incident on the photodiode. This configuration of the SNSPD and photodiode shows an expected plateau in the single photon count rate with an optical bias power on the photodiode above 6.8 µW. Furthermore, we compare the same detector under both optical and electrical bias, and show there is no significant changes in performance. This has the advantage of avoiding an electrical input cable, which reduces the latent heat load by a factor of 100 and, in principle, allows for low loss RF current supply at the cold stage.
Keywords: Computer Networks and Communications; Atomic and Molecular Physics; and Optics

Unidirectional vortex waveguides and multistable vortex pairs in polariton condensates - Gao, Xinghui; Hu, Wei; Schumacher, Stefan; Ma, Xuekai (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Apparatus for the measurement of the thermodynamic speed of sound of diethylene glycol and triethylene glycol - Javed, Muhammad Ali; Vater, Sebastian; Baumhögger, Elmar; Windmann, Thorsten; Vrabec, Jadran (The Journal of Chemical Thermodynamics)
Keywords: Physical and Theoretical Chemistry; General Materials Science; Atomic and Molecular Physics; and Optics

Thermodynamic Properties for 1-Hexene – Measurements and Modeling - Betken, Benjamin; Beckmüller, Robin; Ali Javed, Muhammad; Baumhögger, Elmar; Span, Roland; Vrabec, Jadran; Thol, Monika (The Journal of Chemical Thermodynamics)
Keywords: Physical and Theoretical Chemistry; General Materials Science; Atomic and Molecular Physics; and Optics

Brillouin and Raman imaging of domain walls in periodically-poled 5%-MgO:LiNbO3 - Rix, Jan; Rüsing, Michael; Galli, Roberta; Golde, Jonas; Reitzig, Sven; Eng, Lukas M.; Koch, Edmund (Optics Express)
Recently, ferroelectric domain walls (DWs) have attracted considerable attention due to their intrinsic topological effects and their huge potential for optoelectronic applications. In contrast, many of the underlying physical properties and phenomena are not well characterized. In this regard, analyzing the vibrational properties, e.g. by Raman spectroscopy, provides direct access to the various local material properties, such as strains, defects or electric fields. While the optical phonon spectra of DWs have been widely investigated in the past, no reports on the acoustic phonon properties of DWs exist. In this work, we present a joint Raman and Brillouin visualization of ferroelectric DWs in the model ferroelectric lithium niobate. This is possible by using a combined Raman and virtually imaged phased array Brillouin setup. Here, we show that DWs can be visualized via frequency shifts observed in the acoustic phonons, as well. The observed contrast then is qualitatively explained by models adapted from Raman spectroscopy. This work, hence, provides a novel route to study ferroelectric DWs and their intrinsic mechanical properties.
Keywords: Atomic and Molecular Physics; and Optics

On topological materials as photocatalysts for water splitting by visible light - Ranjbar, Ahmad; Mirhosseini, Hossein; Kühne, Thomas D (Journal of Physics: Materials)
Abstract We performed a virtual materials screening to identify promising topological materials for photocatalytic water splitting under visible light irradiation. Topological compounds were screened based on band gap, band edge energy, and thermodynamics stability criteria. In addition, topological types for our final candidates were computed based on electronic structures calculated usingthe hybrid density functional theory including exact Hartree–Fock exchange. Our final list contains materials which have band gaps between 1.0 and 2.7 eV in addition to band edge energies suitable for water oxidation and reduction. However, the topological types of these compounds calculated with the hybrid functional differ from those reported previously. To that end, we discuss the importance of computational methods for the calculation of atomic and electronic structures in materials screening processes.
Keywords: Condensed Matter Physics; General Materials Science; Atomic and Molecular Physics; and Optics

On topological materials as photocatalysts for water splitting by visible light - Ranjbar, Ahmad; Mirhosseini, Hossein; Kühne, Thomas (Journal of Physics: Materials)
Abstract We performed a virtual materials screening to identify promising topological materials for photocatalytic water splitting under visible light irradiation. Topological compounds were screened based on band gap, band edge energy, and thermodynamics stability criteria. In addition, topological types for our final candidates were computed based on electronic structures calculated usingthe hybrid density functional theory including exact Hartree–Fock exchange. Our final list contains materials which have band gaps between 1.0 and 2.7 eV in addition to band edge energies suitable for water oxidation and reduction. However, the topological types of these compounds calculated with the hybrid functional differ from those reported previously. To that end, we discuss the importance of computational methods for the calculation of atomic and electronic structures in materials screening processes.
Keywords: Condensed Matter Physics; General Materials Science; Atomic and Molecular Physics; and Optics

Optical Arbitrary Waveform Measurement Using Silicon Photonic Slicing Filters - Fang, Dengyang; Zazzi, Andrea; Müller, Juliana; Dray, Daniel; Fullner, Christoph; Marin-Palomo, Pablo; Tabatabaei Mashayekh, Alireza; Dipta Das, Arka; Weizel, Maxim; Gudyriev, Sergiy; Freude, Wolfgang; Randel, Sebastian; et al. (Journal of Lightwave Technology)
We demonstrate an optical arbitrary waveform measurement (OAWM) system that exploits a bank of silicon photonic (SiP) frequency-tunable coupled-resonator optical waveguide (CROW) filters for gapless spectral slicing of broadband optical signals. The spectral slices are coherently detected using a frequency comb as a multi-wavelength local oscillator (LO) and stitched together by digital signal processing (DSP). For high-quality signal reconstruction, we have implemented a maximum-ratio combining (MRC) technique based on precise calibration of the complex-valued opto-electronic transfer functions of all detection paths. In a proof-of-concept experiment, we demonstrate the viability of the scheme by implementing a four-channel system that offers an overall detection bandwidth of 140 GHz. Exploiting a femtosecond laser with precisely known pulse shape for calibration along with dynamic amplitude and phase estimation, we reconstruct 100 GBd QPSK, 16QAM and 64QAM optical data signals. The reconstructed signals show improved quality compared to that obtained with a single high-speed intradyne receiver, while the electronic bandwidth requirements of the individual coherent receivers are greatly reduced.
Keywords: Atomic and Molecular Physics; and Optics